2018
DOI: 10.1111/jgh.14041
|View full text |Cite
|
Sign up to set email alerts
|

The risk of non‐melanoma skin cancer in New Zealand in inflammatory bowel disease patients treated with thiopurines

Abstract: We found a twofold to threefold increase in NMSC incidence in IBD patients treated with thiopurines in NZ, despite the high background incidence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In the past few years, to Big Data has become one of the most‐used vocabulary in the industrial sector, finance, and healthcare 2,3 . Most areas have begun to use big data to analyze and discover new value 4,5 . The information brought by big data is also changing the ecosystem of medical education and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, to Big Data has become one of the most‐used vocabulary in the industrial sector, finance, and healthcare 2,3 . Most areas have begun to use big data to analyze and discover new value 4,5 . The information brought by big data is also changing the ecosystem of medical education and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that thiopurine use but also the cumulative thiopurine dose did not associate with KSC development may be surprising as they are not in line with current guidelines that strictly advise yearly dermatologically screening of thiopurine-treated IBD patients, however, the literature is divided on the effect of thiopurine use on KSC development itself (see also supplementary Table 1, Supplemental digital content 1, http://links.lww.com/EJGH/A902) [7,14,19–22,24–28,30,35,36]. Several studies show results similar to ours and do not show an association between KSC diagnoses and thiopurine use in patients with IBD [11,31,37–41].…”
Section: Discussionmentioning
confidence: 88%
“…Most international guidelines recommend yearly dermatologically screening of thiopurine-treated patients [19,20,[23][24][25]27,28]. However, this is not always feasible in most countries due to the limited capacity of the health care system, the large and increasing volume of patients with KSC, and the increasing prevalence of IBD [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent cohort study (in which patients 65 years and older represented 12% of the study population) by Lemaitre et al[40] found that risk of lymphoma was higher in patients treated with thiopurine monotherapy (mean exposure time was 17 mo) and those treated with combination therapy (thiopurine and anti-TNF, mean exposure time was 8 mo) in comparison to those patients unexposed to such treatments. In addition, in their retrospective observational study, Bahi et al[41] showed a potentially multiplicative risk of non-melanoma skin cancer with increasing age in thiopurine-exposed IBD patients (6 months or longer exposure, median exposure of 42 months). In contrast, a recent cohort study by Cheddani et al[42] of elderly-onset IBD found that thiopurine exposure was not associated with an increased risk of developing cancer when using a time-dependant Cox model.…”
Section: Medical Therapymentioning
confidence: 99%